Effects of Internal Marketing on Customer Orientation Behaviour of Selected Hotels’ Employees in Nigeria - Nebo, Gerald Nwora; Okechukwu, Elizabeth Uzoamaka (European Scientific Journal, ESJ, 2017)
This study was carried out to determine the Influence of Internal Marketing on Customer Orientation Behaviour of Hotel Employees in Nigeria. The objectives of the study include: to determine the effect of internal marketing on customer orientation behaviour of hotel employees; to investigate the moderating influence of personality on the relationship between internal marketing and customer orientation behaviour of the hotel employees; and to investigate the moderating influence of job satisfaction on the relationship between internal marketing and customer orientation behaviour of the hotels’ employees. Survey research design method was adopted for the study. 83 and 174 hotel managers and employees respectively were selected for the study from 20 hotels operating in different geo-political zones of Nigeria. Questionnaire was used for collection of data. Convenience sampling method was used for selecting both the hotels’ managers and guest service employees used for the study. The hypotheses were tested using multiple linear regression. It was revealed that internal marketing has significant influence on customer orientation behavior of hotels’ employees; personality significantly moderates the relationship between internal marketing and customer orientation behavior of the hotel employees; and job satisfaction significantly moderates the relationship between internal marketing and customer orientation behavior of the hotels’ employees. It was recommended that hotel managers should give much priority to internal marketing practice while controlling for the personality and job satisfaction of the guest service employees.